DEVELOPMENT AND EVALUATION OF THEORETICAL AND PRACTICAL KNOWLEDGE AND SKILLS OF STUDENTS - Khakimova Farida Abdullayevna (Web of Journals Publishing, 2024)
The development of theoretical and practical knowledge of students is one of the main tasks of the modern educational system. In this article, we will talk about the methods used in the development of knowledge and skills of students, as well as the methods of their assessment.